LARANGAN ZINA DALAM AL-QUR’AN: (STUDY TAFSIR AL-WASITH TERHADAP QUR’AN SURAH AL-FURQON AYAT 68-69, SURAH AL-ISRO’ AYAT 32 DAN SURAH AL-MU’MINUN AYAT 1-7) - Karimah, Fathimatil Imroatil; Aqliyah, Ulfatul Aqliyah (JURNAL ILMU AL-QUR'AN DAN TAFSIR NURUL ISLAM SUMENEP, 2025)
Abstract This research aims to explore more deeply the issues that frequently arise in society regarding the act of zina (adultery or fornication) as explained in the Qur'an and various scholarly opinions. This study employs a library research method using a descriptive-analytical approach—presenting and describing the topic clearly and in detail through words. It elaborates on several definitions of zina according to different perspectives. The main point drawn from this research is that zina is a sexual relationship between a man and a woman who are not legally married. In his interpretation of Surah Al-Furqan verses 68–69, Wahbah Az-Zuhaili states that zina incurs a sin equivalent to the sin of shirk (associating partners with Allah). Meanwhile, in Surah Al-Isra verse 32, the Qur'an describes zina as an indecent and evil act, and servants of Allah are forbidden from engaging in behaviors that lead to such immorality. Furthermore, Wahbah Az-Zuhaili in his tafsir of Surah Al-Mu’minun verses 1–7 explains the characteristics of those who are successful in the sight of Allah—namely, those who guard their chastity and refrain from committing zina. Keywords: Prohibition, Zina, Qur’an, Surah, Tafsir Al-Wasith